Makrozoobhentos di Pesisir Pantai Kalaki Kec. Palibelo Kab. Bima Nusa Tenggara Barat - Noris, Muhammad (Bioedukasi: Jurnal Pendidikan Biologi, 2020)
Sampling of macrozoobenthos was carried out in the coastal areas of Kalaki, Pallibelo sub-district, Bima, consisting of Station I (the coastal area near the salt ponds) and Station II (the coastal area far from the salt ponds). Determination of the station is done by purposive sampling method. This type of research is a quantitative exploratory survey. The type of data taken is 1) macrozoobhentos data, 2) habitat data (abiotic factors). Data analysis uses the shannon-wiener index (H '), the Population Density Index (KP), and the Krebs Uniformity Index (E). The results showed temperature (30-33 oC: 25-28 oC), Ph (6-6.5: 6-6.7), salinity (20-25%: 27-33%). Macrozoobenthos found consisted of actinopteri, malacostraca, bivalvia, and atinopterygii classes. The number of macrozoobenthos identified was 153 species consisting of a family of 84 species, 56 species of penaeidae, 4 types of chanidae, 3 types of Arcidae, Mytilidae, Veneridae, Anguillidae of 2 species each. Diversity index H '= 1.132: 0.952, Uniformity Index Value (E) = (0.582: 0.489), Population Density Value (KP) Scylla sp. 5,143-6,857 and 0.143 for the Pena viridis, Metrix metrix, Anguilla bicolor. 3. As a result of exploitation in the form of salt ponds, the abundance of macrozoobenthos in the coastal area of Kalaki, Palibelo Subdistrict, Bima Regency, has decreased significantly with marked sedimentation and turbidity levels. This allows damage to the coast ecosystem